Riverbank stability in loose layered silty clays : Comments on the North Spur Dam at Muskrat Falls in Churchill River, Labrador, Newfoundland - Bernander, Stig; Elfgren, Lennart (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2017)
The differences are outlined in landslide analysis between the classic limit equilibrium method with assumed plastic properties of the soil and a progressive analysis applying softening material properties. The risk for failure is studied in the dam at the North Spur riverbank ridge at Muskrat Falls in Churchill River in Labrador, Newfoundland, Canada. A sloping failure surface is much more critical than the horizontal surfaces which have hitherto been studied. Results from new analyses have now been obtained applying softening material properties probable for the ridge. The results indicate safety factors lower than 0.5, i.e. there is a high risk that the ridge will fail if the water level is raised to the proposed level. Three reports are appended where Stig Bernander argues in detail for the need for a proper progressive failure analysis based on measured material properties. He also proposes how such properties may be obtained and gives an example of a way to stabilize the ridge if the soil properties show a softening behaviour. Finally examples of progressive failure analyses are included using probable material properties.